PTEN: a new dawn in Parkinson’s disease treatment - Yang, Xinghuang; Liu, Tianqi; Cheng, Hong (Frontiers in Cellular Neuroscience, 2025)
In recent years, the study of phosphatase and tension homolog (PTEN) has gradually become a research hotspot. As an important oncogene, the role of PTEN in cancer has long been widely recognized and intensively studied, but it has been relatively less studied in other diseases. Parkinson’s disease (PD) is a neurodegenerative refractory disease commonly observed in middle-aged and elderly individuals. The etiology and pathogenesis of PD are numerous, complex, and incompletely understood. With the continuous deepening of research, numerous studies have proven that PTEN is related to the occurrence of PD. In this review, we discuss the relationship between PTEN and PD through the phosphorylation and ubiquitination of PTEN and other possible regulatory mechanisms, including the role of RNA molecules, exosomes, transcriptional regulation, chemical modification, and subtype variation, with the aim of clarifying the regulatory role of PTEN in PD and better elucidating its pathogenesis. Finally, we summarize the shortcomings of PTEN in PD research and highlight the great potential of its future application in PD clinical treatment. These findings provide research ideas and new perspectives for the possible use of PTEN as a PD therapeutic target for targeted drug development and clinical application in the future.